Adaptation and Psychometric Evaluation of the Indonesian Version of the Career Aspirations Scale-Revised (CAS-R) among Adolescents - Prihastuty, Rahmawati; Rahmawati, Dyah Ayu; Pertiwi, Talitha Lintang; Alwan, Faiz Fatihul; Rohmah, Afifatur; Rizq, Attaya Rana; Sulistyawati, Yuni (Universitas Ahmad Dahlan, 2025)
The dynamic changes within the world of work require individuals to engage in robust career planning. In this context, career aspiration is understood as a psychological construct reflecting an individual’s hopes, motivations, and goals related to their future employment. This study aimed to adapt and evaluate the psychometric properties of the Career Aspirations Scale-Revised (CAS-R) into Indonesian to provide a valid and reliable measurement tool. The respondents comprised 549 Indonesian adolescents. The adaptation process followed the ITC (2018) guidelines, encompassing content validation, construct validation through Confirmatory Factor Analysis (CFA) and Rasch analysis, as well as reliability testing. The CFA results supported a three-factor structure (RMSEA = 0.034; CFI = 0.990; TLI = 0.990), with 18 items meeting the factor loading criteria. Cronbach’s alpha of 0.910 indicated high reliability. Rasch analysis further supported the instrument’s validity and internal consistency, with 19 items deemed to fit the model. These findings confirm that the Indonesian version of CAS-R is a suitable instrument for measuring adolescents’ career aspirations in Indonesia. It can be used by schools, counselors, and psychological institutions to support career assessment and planning.